Human resources: strategic management aspects - Chlivickas, Eugenijus; Papšienė, Palmira; Papšys, Arnas (Business, Management and Economics Engineering, 2010)
The following processes pose challenges for the organization: self-establishment in the market economy, restructuring, globalization, development of techniques and technology, formation of information society, development of a knowledge economy, change of the society economic situation and democratic processes. In the organization which is constantly changing a new approach to the organization is formed. It is viewed as an operating system where company employees, i.e., human resources, become the most important and the most active part of the system, determining the efficiency of the pursuing of organizational goals. In the constantly changing organization a new approach to the organization is formed. It is viewed as an operating system where company employees, i. e., human resources, become the most important and the most active part of the system, determining the efficiency of the pursuing of organization objectives. Human resource management process cannot be separated from the strategy. Strategic human resource management is a part of strategic management concept in the organization. Theoretical provisions for the management of human resources, presented in the academic literature, confirm the influence of this functional area of management on the overall organization performance results. For the organization, which is operating in the global market, it is essential to manage existing or potential labor resources effectively. One of the main staff evaluation criteria is the effectiveness of personnel management. New tendencies encourage closer association of human resource management with organization strategy. “Four-C” model competence, commitment, compliance and cost efficiency is helpful in assessing the effectiveness of organization human resources policies conformity with its strategy.Article in Lithuanian.Žmogiškieji ištekliai: strateginio valdymo aspektai